Preliminary evaluation of the production of non-carrier added 111Ag as core of a therapeutic radiopharmaceutical in the framework of ISOLPHARM_Ag experiment. (October 2020) - Ballan, Michele; Tosato, Marianna; Verona, Marco; Caeran, Michele; Borgna, Francesca; Vettorato, Elisa; Corradetti, Stefano; Zangrando, Lisa; Sgaravatto, Massimo; Verlato, Marco; Asti, Mattia; Marzaro, Giovanni; et al.
Abstract: Research in the field of radiopharmaceuticals is increasingly promoted by the widespread and growing interest in applying nuclear medicine procedures in both disease diagnosis and treatment. The production of radionuclides of medical interest is however a challenging issue. Along with the conventional techniques other innovative approaches are being investigated and, among those, the ISOLPHARM project is being developed at INFN-LNL (Istituto Nazionale di Fisica Nucleare – Laboratori Nazionali di Legnaro). Such technique foresees the employment of the SPES ISOL facility to produce isobarically pure Radioactive Ion Beams (RIBs), obtained thanks to electromagnetic mass separation and collected on appropriate substrates. The latter are successively recovered and dissolved, allowing thus the chemical separation and harvesting of the nuclides of interest, free from any isotopic contaminant. Although ISOLPHARM can be potentially employed for most of the routinely used medical radioisotopes, its innovation potential is better expressed considering its capability to provide carrier free unconventional nuclides, difficult to produce with state-of-art techniques, such as 111 Ag, a β — emitter potentially interesting for therapeutic applications. Thus, in the framework of ISOLPHARM, INFN supported a two-years experiment, called ISOLPHARM_Ag, aimed at evaluating the feasibility of the production of a 111 Ag labelled radiopharmaceutical. The ISOL production yields are estimated by computing intensive Monte Carlo codes, that require an appropriate custom Information Technology infrastructure. The presented work is focused on the first part of the production chain including the capability to extract, ionize, and collect stable Ag beams with SPES technologies. MC calculations were used to estimate the expected 111 Ag in-target yields, whereas experiments with stable Ag were performed to test the ionization, transport and collection of Ag beams. Highlights: ISOLPHARM_Ag aims to study the capability to produce 111Ag via ISOL and its employment for radiopharmaceutical development. 111Ag production yields were evaluated with MC codes, run with the benefit of cloud computing in a custom IT infrastructure. Beams with stable Ag isotopes were produced and the ionization efficiency for Ag was measured. Ag beam were deposited on collection substrates that were finally dissolved to evaluate the ion recovery efficiency.